Android-Based Cikeruhan Dance Multimedia to Improve Students' Self-Directed Learning - Badaruddin, Saian; masunah, Juju; Nugraheni, Trianti; Ganda Prawira, Nanang; Mohd Zahid, Muhammad Fairul Azreen (Yayasan Keluarga Guru Mandiri, 2025)
This research aims to develop an Android-based digital module for Cikeruhan Dance that can enhance students' self-directed learning (SDL) abilities. Cikeruhan Dance, as part of the Sundanese folk dance tradition, has the potential to be used as an interesting and relevant learning material for university students and school pupils, especially in the context of dance education. The research method employed is Research and Development (RD), utilizing the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The module development process involves analyzing students' needs for interactive and easily accessible dance learning materials, followed by designing a module that includes History, Movement Structure, Makeup and Costume, as well as video tutorials and quizzes for evaluation. Data collection techniques include observation, interviews, and literature studies to analyze needs and identify novelties, ensuring that the development aligns with student requirements. Triangulation analysis is then applied to ensure the collection of relevant and balanced data. A limited trial was conducted with dance education students. The results of the small group trial showed an effectiveness of 85.07%, while the large group trial showed an effectiveness of 87.91%. The difference occurred because the large group already had prior knowledge of the material. This module is considered highly valid with an attractive design, communicative language, and visual elements that support learning. The use of the Android-based module facilitates access and increases motivation and independence among students in learning Cikeruhan Dance.